Plaza Complex its cultural significance in the City of San Fernando and town of Balaoan in La Union - Hufana, Mary Cita M. (UP Los Baños Journal, 2013)
This article examines the formal-structural, and functional characteristics of plaza complex in the city of San Fernando and the town of Balaon in the province of La Union. Through the analysis of theses aspects, the cultural significance of the plaza power inscribed in the practices which take place within it. The study utilizes Henry Lefebvre's concept of three spaces: Conceived space, Lived space, and Perceived space, Plaza complex is seen not only as an architectural concept but also as a space which is produced by all users-thereby creating a cultural concept. Initially the plaza complex was conceptualized and built as a means to control and manipulate the Filipinos during the Spanish colonization. As San Fernando and Balaoan undergo development, their plaza complexes still remain to be the political, economic centers and host of major religious, as well as recreational activities. The plaza complex in San Fernando has strongly transformed into an economic space as evident in the presence of many commercial establishment such as fast food outlets and banks, Balaoan on the other hand, still retains its traditional lay-out and structures including the residential spaces of the established elite families in the town. Its use as a religious space has been strengthened, becoming a stage a theoretical performance during the annual celebration of the Holy Week. Discussing the political, religious, economic and recreational activities within the plaza complex throughout the year highlights its cultural significance to the people- how they make use of the plaza complex and how different kinds of spaces are produced.